Development of head loss equations for self-cleaning screen filters in drip irrigation systems using dimensional analysis. (May 2015) - Zong, Quanli; Zheng, Tiegang; Liu, Huanfang; Li, Cuijin
Abstract : Two equations for computing head loss in self-cleaning screen filter when using tap water and sand water mixture were developed using dimensional analysis. The parameters influencing head losses were considered to be eleven parameters representing the filter properties; filtration level, total filtration surface, flow rate, concentration of total sand, filtration time, inside diameter of the inlet and outlet pipes, mean filtration velocity, mean diameter of sand particle size distribution, water viscosity and water density. These variables were incorporated into eight dimensionless groups obtained through Buckingham's method. Two experiments to analyse head losses were carried out using 178 μm and 124 μm screen filters. A total of 54 runs for tap water and 58 filtration cycles for sand water mixture were carried out to obtain 54 and 2152 experimental points respectively, enabling the developed equations to be correlated. The developed equations were satisfactorily adjusted using the experimental data. Despite the adjustments of the equations being significant, regression coefficients were not always high. A comparison between the predicted and the measured head losses with three screen filters was in close agreement with a correlation coefficient of 0.902 for tap water and 0.832 for sand water mixture, respectively. The performance of equation was also compared with equations developed from the literature. The equations fromPuig-Bargués et al. (2005b ) Biosystems Engineering, 92 (3), p383–390 and this study provided good predictions, compared to other equations available in the literature. Highlights: Two new equations of head loss for self-cleaning screen filter have been developed. Parameter of filtration time was considered as it contributes to head loss of filter. Experiments used sand water mixture, which differ from other studies with effluents. Equation in this study can provide better predictions, as compared to other equations.